Study on rural migration and return migration in Kosovo - Judith Möllers; Diana Traikova; Thomas Herzfeld; Egzon Bajrami (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
[Objectives] The overall objective of the study is to address the causes of migration and its consequences for rural areas of Kosovo. More specifically, we focus on the motives of migrants, the impact of migration on households left behind and the socio-economic situation of returning migrants. In the first part of this study, we will discuss the motivation behind migration. A specific focus is on drivers of the recent out-migration wave which started in 2014. We will furthermore shed some light on (positive and negative) migration impacts in the second part of the study: for some households, remittances received from migrated family members may alleviate poverty, while for others migration is linked to significant psychological burdens or lack of labour force in family businesses. In the third part, the study will focus on the consequences of return migration by identifying important attributes of the recently returned migrants and their specific needs and potentials for successful reintegration. We will look at the skill sets (education and experience) of the returnees, as well as their personal well-being and intentions to stay. Vulnerable groups such as women and ethnic minorities will be analysed separately. The study will provide recommendations on how the needs of returnees can be addressed and how they may contribute to a positive rural development in their communities. It will furthermore be used as a source of information for other ongoing projects dealing with return migration. The study was closely coordinated with a number of stakeholders in the Republic of Kosovo. Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) provided funds for this project in the framework of its project "Competitiveness of the Private Sector in Rural Areas". The Ministry of Agriculture, Forestry and Rural Development (MAFRD) provided technical support. The study was carried out by the Leibniz Institute of Agricultural Development in Transition Economies (IAMO). Other programme partners include: municipalities, the Ministry of Internal Affairs (MIA), the Ministry of Diaspora (MD), the Ministry of Finance (MF), the Ministry of Education, Science and Technology (MEST), the Ministry of Labour and Social Welfare (MLSW), NGOs, farmers' and forest owners' associations, women's groups and ethnic communities, the Kosovo Forestry Agency (KFA), and the Association of Municipalities in Kosovo (AMK).
urn:nbn:de:gbv:3:2-76033
Keywords: 330